Protocol for the ROBUST (Registry Of type B aortic dissection with the Utility of STent graft) study: an ambispective, multicentre, open cohort study. Issue 12 (14th December 2017) - Rong, Dan; Ge, Yangyang; Xue, Yan; Liu, Feng; Lu, Kai; Liu, Peng; Zhang, Lei; Ge, Xiaohu; Miu, Jianhang; Zhong, Linkun; Fan, Weidong; Zhang, Hongpeng; et al.
Abstract : Introduction: Thoracic endovascular aortic repair (TEVAR) is widely used for type B aortic dissection, although with satisfactory outcome in a limited proportion of patients. To better inform patient prognostication, the Registry Of type B aortic dissection with the Utility of STent graft (ROBUST) study aims to identify imaging-based predictors of post-TEVAR adverse outcomes up to 10-year follow-up. Methods and analysis: ROBUST is designed as an ambispective, multicentre, open cohort study. All patients undergoing TEVAR from 1 January 2008 to 1 July 2027 at participating centres will be invited to join the study. It is conservatively estimated that over 2000 patients will join the study. Data on demographics, disease history, procedural details, imaging features and follow-up will be collected after discharge. Cox proportional-hazards analysis will be used to identify independent predictors of primary outcomes. Stratification analysis will be performed to identify which subgroup of patients would benefit the most from TEVAR. Ethics and dissemination: The protocol has been approved by the ethics committee of the coordinating centre. Findings will be disseminated in professional peer-reviewed journals to promote understanding of the rehabilitation process. Trial registration number: ChiCTR-POC-17011726; Pre-results.